Genetic Polymorphisms of IL17 and Chagas Disease in the South and Southeast of Brazil - Pâmela Guimarães Reis; Christiane Maria Ayo; Luiz Carlos de Mattos; Cinara de Cássia Brandão de Mattos; Karina Mayumi Sakita; Amarilis Giaretta de Moraes; Larissa Pires Muller; Julimary Suematsu Aquino; Luciana Conci Macedo; Priscila Saamara Mazini; Ana Maria Sell; Divina Seila de Oliveira Marques; et al. (Journal of Immunology Research)
The aim of this study was to investigate possible associations between genetic polymorphisms of IL17A G197A (rs2275913) and IL17F T7488C (rs763780) with Chagas Disease (CD) and/or the severity of left ventricular systolic dysfunction (LVSD) in patients with chronic Chagas cardiomyopathy (CCC). The study with 260 patients and 150 controls was conducted in the South and Southeast regions of Brazil. The genotyping was performed by PCR-RFLP. The A allele and A/A genotype of IL17A were significantly increased in patients and their subgroups (patients with CCC; patients with CCC and LVSD; and patients with CCC and severe LVSD) when compared to the control group. The analysis according to the gender showed that the A/A genotype of IL17A was more frequent in female with LVSD and mild to moderate LVSD and also in male patients with LVSD. The frequency of IL17F T/C genotype was higher in male patients with CCC and severe LVSD and in female with mild to moderate LVSD. The results suggest the possible involvement of the polymorphisms of IL17A and IL17F in the susceptibility to chronic Chagas disease and in development and progression of cardiomyopathy.